Neutrophils and clinical outcomes in patients with acute coronary syndromes and/or cardiac revascularisation - Guasti, Luigina; Dentali, Francesco; Castiglioni, Luana; Maroni, Lorenzo; Marino, Franca; Squizzato, Alessandro; Ageno, Walter; Gianni, Monica; Gaudio, Giovanni; Grandi, Anna M.; Cosentino, Marco; Venco, Achille (Thrombosis and Haemostasis, 2011)
Some studies have suggested that high levels of total white blood cell (WBC) count and C-reactive protein (CRP) may be considered as independent prognostic factors in patients with acute coronary syndromes (ACS) and/or after cardiac revascularisation by percutaneous coronary intervention or coronary artery bypass grafting surgery. Evidence on the role of neutrophils in cardiovascular disease is less compelling. Therefore, we conducted a systematic review of the literature with the aim of identifying all the available evidence to clarify the role of neutrophils (absolute or relative count, neutrophil/lymphocyte ratio) as a prognostic risk factor in patients with ACS and/or cardiac revascularisation. All published studies evaluating the role of neutrophils as a risk factor for clinical outcomes were assessed using the MEDLINE and EMBASE databases. Study selection, data extraction and validity assessment was performed independently by two reviewers. Twenty-one studies (17 of which had positive results) for a total of more than 34,000 patients were included. Ten of 13 studies in ACS patients found that neutrophils measured on-admission are related to mortality rate and/or to major adverse clinical events. A predictive value of neutrophils after cardiac revascularisation procedures was reported in seven out of eight studies. Most of the studies showed that neutrophils were independent predictors of cardiovascular outcomes when analysed concomitantly with other markers of inflammation (WBC, CRP). The findings of our systematic review highlight the potential application of this inexpensive and readily available inflammatory marker for risk stratification in patients with ACS and/or cardiac revascularisation.
Keywords: Systematic review; neutrophils; outcome; acute coronary syndromes; revascularisation